Breast tumour organoids: promising models for the genomic and functional characterisation of breast cancer. (9th January 2019) - Roelofs, Charlotte; Hollande, Frédéric; Redvers, Richard; Anderson, Robin L.; Merino, Delphine
Abstract : Until recently, established cancer cell lines have been used extensively in breast cancer research, due largely to the difficulties associated with the manipulation and long-term maintenance in culture of primary tumour cells from patients. The recent development of organoid cultures has provided new opportunities to model and analyse patient samples, allowing the propagation of malignant cells under conditions that resemble the three-dimensional growth of breast tumours. They have proved efficacious in preserving the heterogeneity of primary samples and are emerging as a new model to further characterise the molecular features of breast cancer. Organoids formed from patient-derived cells are now in use for the evaluation of drug sensitivity and to validate disease-causing genomic variations. Here, the advantages and limitations of organoid cultures will be discussed and compared with the parallel development of other two- and three-dimensional culture strategies and with patient-derived xenografts. In particular, we will focus on the molecular characterisation of breast cancer organoids and provide some examples of how they have been used in functional studies.